THE EFFECT OF MENTIMETER WEB – BASED APPLICATION TO EFL STUDENT’S READING SKILLS - Indri, Diana Chusuma; Asmara, Candra Hadi; Asari, Slamet (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
ABSTRACT This study examines the impact of the Mentimeter web-based application on enhancing EFL students' reading skills. Using a pre-experimental design, 36 students from Class X-C at MAS Al-Fatich Surabaya participated in a pre-test and post-test. The findings reveal a significant improvement in students' reading skills, with the average score increasing from 81.56 to 89.00 after the treatment. Statistical analysis using a paired t-test showed a sig. (2-tailed) value of 0.000, indicating a highly significant difference between pre-test and post-test scores. The Mentimeter application effectively engaged students through interactive quizzes and real-time feedback, fostering active participation and improving comprehension. However, the study also highlights the challenge of reliance on stable internet connectivity for optimal implementation. Overall, the research concludes that the Mentimeter application is a valuable tool for improving EFL students' reading skills and offers insights for integrating technology into language learning. Keywords: Mentimeter, reading skills, EFL students, technology integration, interactive learning